2016
DOI: 10.1016/j.ssc.2016.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Influence of structural distortions on the Ir magnetism in Ba2−xSrxYIrO6 double perovskites

Abstract: We explore the relative strengths of spin orbit coupling and crystal field splitting in the Ir 5+ compounds Ba 2-x Sr x YIrO 6 . In the case of strong spin orbit coupling and regular Ir 5+ octahedra, one expects a nonmagnetic J = 0 state; in the case of distorted octahedra where crystal field effects dominate, the t 2g manifold splits into a magnetic ground state. We report the results of continuously transitioning from the cubic Ba 2 YIrO 6 double perovskite with ideal octahedra to the monoclinic Sr 2 YIrO 6 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 28 publications
5
31
0
Order By: Relevance
“…Our results are in strong contrast with the reported ones by Cao et al [20], but in full agreement with recent reports on polycrystalline samples [23,24], pointing towards a nonmagnetic ground state with the presence of a small amount of correlated J = 1/2 impurities.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our results are in strong contrast with the reported ones by Cao et al [20], but in full agreement with recent reports on polycrystalline samples [23,24], pointing towards a nonmagnetic ground state with the presence of a small amount of correlated J = 1/2 impurities.…”
Section: Discussionsupporting
confidence: 88%
“…More recent works on polycrystalline samples of the series Ba 2−x Sr x YIrO 6 [23,24] did not observe any signature for long-range magnetic order in this material in their magnetic susceptibility characterization, in strong contrast with Cao et al [20]. On the contrary, these reports reinforce the notion of a nonmagnetic ground state dominated by strong SOC.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…More recently, interest also developed in other transition metal oxides with octahedron or distorted octahedron crystal-field splittings leading to (t 2g ) 4 ions [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. When the Hubbard U and Hund J H couplings are large it is expected that the system develops S = 1 states, while increasing the SOC λ should lead to states with an effective angular momentum zero.…”
Section: Introductionmentioning
confidence: 99%
“…16 In contrast, studies on polycrystals of the series Ba 2−x Sr x YIrO 6 reported the absence of any long-range order and no significant change in the magnetic properties upon increasing the structural disorder from cubic Ba 2 YIrO 6 with regular IrO 6 octahedra to monoclinic Sr 2 YIrO 6 with highly distorted IrO 6 octahedra, thus demonstrating that the CF splitting in Sr 2 YIrO 6 is not enough to compete with the strong spin-orbit coupling. 19,20 A recent detailed single crystal x-ray diffraction analysis of Sr 2 YIrO 6 even questioned the formerly reported monoclinic structure 15,19,21 but reported a cubic unit cell with regular IrO 6 octahedra.…”
Section: 18mentioning
confidence: 96%